Calicophoron daubneyi in sheep and cattle of Sardinia, Italy - Sanna, G. (2016)
This study aimed to investigate the prevalence of paramphistomosis and confirm the species identity of rumen flukes from sheep and cattle of Sardinia (Italy), by molecular methods. From 2011 to 2014, 381 sheep and 59 cattle farms were selected and individual faecal samples were run on 15 sheep and 5 cattle for each farm, respectively. The prevalence at the slaughterhouse was calculated by examination of 356 sheep and 505 cattle. 13adult flukes collected from sheep and cattle and 5 belonging to the historical collection of Laboratory of Parasitology at the Department of Veterinary Medicine of Sassari, previously classified as Paramphistomum spp., were used for PCR amplification and sequencing of the ITS2+ rDNA. Previously classified Paramphistomum leydeni from South America were used as controls. The EPG prevalence was 13.9 % and 55.9 % for sheep and cattle farms respectively. At slaughterhouses, paramphistomes were found in 2 % of the sheep and 10.9 % of the examined cows. Conversely to the latest reports, the sequences comparison showed that all the Sardinian rumen flukes belong to Calicophoron daubneyi.